2016
DOI: 10.1111/1365-2435.12665
|View full text |Cite
|
Sign up to set email alerts
|

Author‐suggested reviewers: gender differences and influences on the peer review process at an ecology journal

Abstract: 1. Peer review is the primary method by which journals evaluate the quality and importance of scientific papers. To help editors find suitable reviewers, many journals allow or require authors to suggest names of preferred and nonpreferred reviewers. Though authors should know best who is qualified to review their papers, they also have a strong incentive to suggest reviewers that they expect to review their paper positively. 2. In this study, we examine the reviewers that are suggested as preferred and nonpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
1
31
2
1
Order By: Relevance
“…In a previous paper, Fox et al () found that ~20% of first authors defer corresponding authorship to one of their coauthors, and that female first authors defer corresponding authorship more often than do male first authors. The corresponding author listed on the cover page of the manuscript is the author that submitted the paper to the journal for >99% of papers considered by Functional Ecology (Fox, Burns, Muncy, & Meyer, ). We thus asked whether deferring corresponding authorship was predictive of how well a submitted manuscript fares after submission, and whether the gender difference in corresponding authorship could account for the gender differences in peer‐review outcomes observed in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper, Fox et al () found that ~20% of first authors defer corresponding authorship to one of their coauthors, and that female first authors defer corresponding authorship more often than do male first authors. The corresponding author listed on the cover page of the manuscript is the author that submitted the paper to the journal for >99% of papers considered by Functional Ecology (Fox, Burns, Muncy, & Meyer, ). We thus asked whether deferring corresponding authorship was predictive of how well a submitted manuscript fares after submission, and whether the gender difference in corresponding authorship could account for the gender differences in peer‐review outcomes observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous paper, Fox et al (2018) found that ~20% of first authors defer corresponding authorship to one of their coauthors, and that female first authors defer corresponding authorship more often than do male first authors. The corresponding author listed on the cover page of the manuscript is the author that submitted the paper to the journal for >99% of papers considered by Functional Ecology (Fox, Burns, Muncy, & Meyer, 2017).…”
Section: Corresponding Authorship and Editorial Decisionsmentioning
confidence: 99%
“…Fox et al . () found that author‐suggested reviewers are more likely to be male in general, and male authors are even more likely to suggest male reviewers. Editors also have been found to demonstrate homophily when selecting reviewers, both with regards to region (Gaston & Smart, ) and gender (Helmer, Schottdorf, Neef, & Battaglia, ).…”
Section: Fairnessmentioning
confidence: 98%
“…Although associate editors do not always use these suggestions, this is one place in which the scientific community at large can ensure that women are receiving an equal chance to guide the field, by the simple act of finding and suggesting appropriate reviewers who are women. As one would expect, there is no difference in reviewing outcome between men and women (Fox et al., , ). Authors can use lists such as DiversifyEEB to identify a balanced set of reviewers; we suggest that authors consider this for every publication they submit regardless of journal.…”
Section: Community‐based Solutionsmentioning
confidence: 99%
“…A relatively recent analysis, for example, found a very unbalanced ratio in the gender of manuscript reviewers for the journal Functional Ecology —between 82% and 73% of invited reviewers over a 10‐year period (from 2004 to 2014, respectively) were men (Fox, Burns, & Meyer, ). The gender of the editors and the reviewers suggested by authors significantly influenced the proportion of women invited to review; because the gender ratio of editors was majority men (100%–62.5%), and men were more likely to be suggested as reviewers (85%–75%), this led to fewer women reviewers overall (Fox, Burns, Muncy, & Meyer, ; Fox et al., ). This striking difference in reviewing opportunities meant fewer women were offered chances for intellectual growth and for the ability to add their opinions and input to the reviewing process—in other words, they were not given an equal chance to shape the field.…”
Section: Introductionmentioning
confidence: 99%